Cardiac dilatation index as an indicator of terminal central congestion evaluated using postmortem CT and forensic autopsy data. (June 2016) - Michiue, Tomomi; Sogawa, Nozomi; Ishikawa, Takaki; Maeda, Hitoshi
Highlights: Virtual CT data of the heart was analyzed to investigate terminal central congestion. CDI was defined as the ratio of the virtual heart weight to measured heart weight. CDI and estimated heart blood pooling showed differences among the causes of death. CDI and virtual heart blood volume may be indicators of terminal central congestion. Abstract: Previous studies demonstrated possible application of postmortem quantitative CT data analysis of the heart and lung in situ to investigate terminal cardiopulmonary pathophysiology. The present study analyzed virtual CT morphometric and autopsy data of the heart to investigate terminal central congestion in forensic autopsy cases ( n  = 113, within 3 days postmortem); the virtual total heart weight in situ was estimated using CT morphometry, and the difference from and ratio to the measured weight at autopsy were calculated as indicators of heart blood pooling and the cardiac dilatation index (CDI) before dissection, respectively. There were substantial differences between the estimated heart blood pooling in situ and volume recovered at autopsy, including a characteristic decrease in drowning, alcohol/sedative-hypnotic intoxication and sudden cardiac death (SCD), possibly due to blood redistribution after thoracic dissection. The estimated in situ heart blood pool and CDI values were higher in SCD but lower in fatal hemorrhage and hemopericardium, as well as in acute mechanical asphyxiation and hyperthermia (heatstroke). In addition, there was a significant difference in heart blood pooling between mechanical asphyxiation or drowning and SCD. The CDI was significantly lower in fatal hyperthermia (heatstroke) than in drowning, fatal methamphetamine abuse, alcohol/sedative-hypnotic intoxication and SCD. These findings suggest the usefulness of applying the CDI and postmortem heart blood volume in situ as supplementary indicators of terminal central congestion, especially for investigating deaths from hemorrhage, hemopericardium, hyperthermia (heatstroke) and SCD.